Keyser, Dora Stoller (audio interview #1 of 4) - Stoller Keyser, Dora (07/04/1899 - 7/20/1983); Fonfa, Lynn, interviewer
INTERVIEW DESCRIPTION - This is the first of three interviews conducted with Dora Keyser in her home for a women's oral history class at UCLA. Keyser was a willing participant and easily established rapport with the interviewer, to whom she was introduced by Sherna Berger Gluck, who was teaching the class at UCLA. A fourth interview was conducted three years later by Gluck. 1974-1